Impact of workplace ostracism on knowledge withholding behavior: Does job contract matter? - Bhattarai, Ganesh (NCC Journal, 2020)
Considering the lack of home ground generated theory and empirical evidence regarding the knowledge-withholding, workplace ostracism, and job contract. The current study was carried out to measure the impact of perceived workplace ostracism on knowledge-withholding behavior and the moderating role of job contracts in the relationship between workplace ostracism and knowledge-withholding behavior. Perceptual and cross-sectional data were collected from the employees working in the Nepalese co-operative industry. Among the surveyed employees, 329 responses were analyzed using SPSS. Positivist research philosophy and deductive reasoning approach were used to reach a conclusion from the quantitative data. This study revealed that workplace ostracism positively affects knowledge-withholding behavior. Job contracts moderated the relationship between workplace ostracism and knowledge-withholding behavior. Permanent employees' knowledge-withholding behavior was positively impacted by workplace ostracism. Temporary employees' knowledge-withholding behavior was not affected due to workplace ostracism. A number of implications and directions for future research are suggested.